A Review on Antecedents and Consequences of Leisure Reading and Writing in Children - Birnbaum, Lisa; Kröner, Stephan (SAGE Open, 2022)
It is desirable that children engage in reading and writing beyond school. What is known about various individual and environmental variables that may be related to children’s leisure reading and writing? And how strong is existing evidence? Our scoping review aims at mapping research on leisure reading and writing in first- to fourth-graders. Using content analysis, we extracted 135 research findings, among them only 6 on leisure writing. In most findings, leisure reading and writing were considered as consequences of variables like reading competence, motivation, and attitudes. Considerably fewer findings included leisure reading and writing as antecedents. We discuss the need for more longitudinal and experimental studies and a stronger focus on the connection between leisure reading and writing.<br

Auslandsaufenthalt im Studium – eine systematische Analyse positiver und negativer Überzeugungen - Birnbaum, Lisa; Penthin, Marcus; Kröner, Stephan (80. Tagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF), 2015)

Beliefs about leisure time writing of elementary school children - Birnbaum, Lisa; Schueller, Elisabeth M.; Kröner, Stephan (Journal for Educational Research Online, 2019)
When elementary school students write in their leisure time, they acquire cornpetences. Moreover, writing is a cultural activity with value in itself. however, there are only few studies regarding determinants of children's leisure time writing. Therefore, a questionnaire based on the theory of planned behavior (Ajzen, 1991) was developed to examine the determinants of leisure time writing in elementary school students. Departing from a qualitative and a quantitative pilot study, items were generated and used in a study with N = 244 children. Beliefs concerning congruent consequences, beliefs concerning incongruent consequences, controllability, and intrinsic value proved to be statistically significant predictors of writing frequency, writing time, and produced amount of text. The intrinsic value mediated the effects of the other predictors. Overall, the scales explained 42 % of the variance in each of the three criterion variables. The questionnaire's construct validity is supported by the boy's lower values in several predictors compared to the girl's values. Perspectives for further research are discussed.
CRIS-Team WoS Importer:2020-02-21

Children’s and adolescents’ engagement with music and the potential for (digital) empowerment processes: A text-mining-supported scoping review - Smolarczyk, Kathrin; Birnbaum, Lisa; Christ, Alexander; Kröner, Stephan (Psychology of Music, 2024)
Extracurricular and out-of-school engagement with music is often associated with positive effects for musical goals while also holding potential for developmental and empowerment processes. The COVID-19 pandemic has highlighted the importance and the potential of digital technologies for facilitating musical engagement. The emergence of digitally transformed musicking has added complexity to the already multifaceted and complex field of research on non-formal musical engagement. Thus, the aims of this text-mining-supported scoping review are (1) to map and describe the underlying research topics in the field of children’s and adolescents’ musical engagement, (2) to explore potential for empowerment processes, and (3) to identify the extent to which digital aspects emerge. Based on N = 624 articles, a topic-modeling procedure yielded k = 10 topics covering cognitive, emotional and attitudinal, youth cultural and digital aspects. Among these, one predominantly digital topic comprised studies on the production and consumption of music. Implications for the potential for empowerment can be drawn from studies that focus on youth cultural aspects, such as hip-hop culture and digital aspects. Limitations and implications for further research are discussed, including how to transfer these findings and how new technologies can further enhance music-making and creation.
CRIS-Team Scopus Importer:2024-05-10
Keywords: empowerment; music; non formal education; scoping review; text-mining

Criteria guaranteeing reproducibility of quantitative-empirical studies: recommendations and best-practice examples Kriterien zur Sicherstellung der Reproduzierbarkeit quantitativ-empirischer Studien: Empfehlungen und Positivbeispiele - Christ, Alexander; Birnbaum, Lisa; Kröner, Stephan (Zeitschrift für Erziehungswissenschaft, 2025)
Enabling replication and reproduction of scientific work is pivotal for quality assurance independent of the original authors. Replication involves repeated data collection and data analysis under the same conditions, based on the given information in the publication and accompanying material. Reproduction means that based on available raw data or alternatively information documented in the publication, the same data are analysed again using the same procedures. Since the issue of reproducibility has so far received less attention in empirical educational research than that of replicability, this paper focuses on the procedure for ensuring the possibility of reproduction attempts in this field. We start from criteria that have been published in guidelines from neighbouring fields such as psychology or special needs education. Open data, metadata and code are introduced as central criteria for enabling reproduction attempts and information is given on which alternative criteria have to be fulfilled to check whether a work can be subjected to reproduction attempts if open data, metadata and code are not accessible. It is discussed how the use of public data repositories can help to ensure that all criteria are met and reproduction of quantitative analyses can be ensured despite the limited number of characters in journal publications.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Guidelines; Quantitative methods; Reproducibility

„…[da] ist man so frei und kann sich ALLES ausdenken“. Eine qualitative Interviewstudie zur Frage, was Kinder dazu bewegt und daran hindert, in ihrer Freizeit zu schreiben - Birnbaum, Lisa; Schüller, Elisabeth; Kröner, Stephan (Tagung der Pädagogischen Psychologie (PAEPS), 2015)

Determinanten freizeitlicher Schreibaktivitäten bei Grundschulkindern - Birnbaum, Lisa (Forschungskolloquium des Zentralinstituts für Lehr-Lernforschung, Nürnberg, 2016)

Determinants of leisure time writing in primary school students. Development of a questionnaire. - Birnbaum, Lisa (International Conference on Writing Research 2016, 2016)

Digitalisierung in der kulturellen Bildung. Interdisziplinäre Perspektiven für ein Feld im Aufbruch. - Jörissen, Benjamin; Kröner, Stephan; Birnbaum, Lisa; Krämer, Franz; Schmiedl, Friederike Luise (Digitalisierung in der kulturellen Bildung. Interdisziplinäre Perspektiven für ein Feld im Aufbruch., 2023)
Welche Konsequenzen und Potenziale bringt die digitale Transformation für die kulturelle Bildung mit sich? Antworten auf diese Frage bietet der vorliegende Band in Form einer Übersicht über Forschungsergebnisse aus dem BMBF-Förderschwerpunkt „Forschung zur Digitalisierung in der kulturellen Bildung“. Über mehrere Jahre hinweg haben darin 13 Verbund- und Einzelprojekte in ganz Deutschland zu digitalen Phänomenen in der kulturellen Bildung geforscht: zu Musik, Literatur, Tanz, Performance, bildender Kunst und darüber hinaus. Die Forschungsvorhaben zeichnen sich durch eine große Perspektivenvielfalt aus: Neben Erziehungswissenschaft und Bildungsforschung sind spezifische Sparten der kulturellen Bildung und weitere geisteswissenschaftliche Fächer ebenso vertreten wie die wie die Informatik. Zudem hat ein Metavorhaben qualitativ-metatheoretische Perspektiven entwickelt sowie Forschungssynthesen zur Digitalisierung der kulturellen Bildung insgesamt und zum digitalen Wandel einzelner kultureller Aktivitäten erarbeitet, teils unter Verwendung von Big-Data-Methoden. Die im Buch gebündelten Ergebnisse stellen eine wertvolle Ressource für Handelnde in Forschung, Kulturpädagogik und Politik dar, indem sie es ermöglichen, sich einen Überblick über das Innovationspotenzial zu verschaffen, welches sich aus der digitalen Transformation von kultureller Bildung ebenso ergibt wie aus ihrer Erforschung. (DIPF/Orig.)<br
Keywords: Kulturelle Bildung; Digitalisierung; Digitale Medien; Jugendkultur; Forschung; Bildung; Bildungsangebot; Inklusion; Mehrfachbehinderung; Partizipation; Anwendung; Soziales Netzwerk; Erwachsenenbildung; Lernumgebung; Musikunterricht; Musik; Musizieren; Musikwissenschaft; Medienpädagogik; Lernprozess; Kunstpädagogik; Ästhetische Bildung; Rezension; Bewertung; Bildungsprozess; Empirische Forschung; Deutschland

Digital social innovations in rural areas – process tracing and mapping critical junctures - Sommer, Carola Rebecca; Chilla, Tobias; Birnbaum, Lisa; Kröner, Stephan (Journal of Rural Studies, 2025)
In recent years, digitalisation projects have helped rural areas to bridge some of the urban-rural disparities, such as accessibility issues as well as the digital literacy divide. To further exploit the potential of digitalisation for rural areas, we aim to understand the implementation of digitalisation processes and their conceptual alignment with Digital Social Innovation (DSI). As an example of Neo-Endogenous Regional Development (NERD) approaches, this perspective provides rich insights into small-scale rural adaptation in a rapidly digitising world. DSI encompasses a strong process perspective, but lacks a broader empirical application. It is a multifaceted concept that includes bottom-up participation, learning and empowerment. To operationalise the process perspective within DSI, we apply a process tracing approach within a qualitative comparative analysis of four case studies. Based on schematic mappings, we conclude with four critical junctures that provide insights for rural DSI. First, innovation can be triggered both endogenously and exogenously, with different implications for path dependencies. Second, participatory processes are crucial for digital innovation in rural communities. Third, hybridisation as an intermediate step can help to reduce the digital divide. Finally, successful institutionalisation benefits from collaborative learning. These findings outline how successful digital social innovation generates impacts beyond the project scope.
CRIS-Team Scopus Importer:2024-12-06
Keywords: digital social innovation; embeddedness; Neo-endogenous regional development; Rural digitalisation; Social innovation

Einleitung - Jörissen, Benjamin; Birnbaum, Lisa; Krämer, Franz; Schmiedl, Friederike Luise; Kröner, Stephan (Digitalisierung in der Kulturellen Bildung: Interdisziplinäre Perspektiven für ein Feld im Aufbruch, 2023)
Keywords: Kulturelle Bildung; Digitalisierung; postdigitale Kultur

Einleitung: Digitalisierung in der kulturellen Bildung. Interdisziplinäre Perspektiven für ein Feld im Aufbruch - Jörissen, Benjamin; Birnbaum, Lisa; Krämer, Franz; Schmiedl, Friederike Luise; Kröner, Stephan (Digitalisierung in der kulturellen Bildung. Interdisziplinäre Perspektiven für ein Feld im Aufbruch, 2023)
Welche Konsequenzen und Potenziale bringt die digitale Transformation für die kulturelle Bildung mit sich? Antworten auf diese Frage bietet der vorliegende Band in Form einer Übersicht über Forschungsergebnisse aus dem BMBF-Förderschwerpunkt „Forschung zur Digitalisierung in der kulturellen Bildung“. Über mehrere Jahre hinweg haben darin 13 Verbund- und Einzelprojekte in ganz Deutschland zu digitalen Phänomenen in der kulturellen Bildung geforscht: zu Musik, Literatur, Tanz, Performance, bildender Kunst und darüber hinaus. Die Forschungsvorhaben zeichnen sich durch eine große Perspektivenvielfalt aus: Neben Erziehungswissenschaft und Bildungsforschung sind spezifische Sparten der kulturellen Bildung und weitere geisteswissenschaftliche Fächer ebenso vertreten wie die wie die Informatik. Zudem hat ein Metavorhaben qualitativ-metatheoretische Perspektiven entwickelt sowie Forschungssynthesen zur Digitalisierung der kulturellen Bildung insgesamt und zum digitalen Wandel einzelner kultureller Aktivitäten erarbeitet, teils unter Verwendung von Big-Data-Methoden. Die im Buch gebündelten Ergebnisse stellen eine wertvolle Ressource für Handelnde in Forschung, Kulturpädagogik und Politik dar, indem sie es ermöglichen, sich einen Überblick über das Innovationspotenzial zu verschaffen, welches sich aus der digitalen Transformation von kultureller Bildung ebenso ergibt wie aus ihrer Erforschung. (DIPF/Orig.)<br
Keywords: Kulturelle Bildung; Digitalisierung; Digitale Medien; Jugendkultur; Forschung; Bildung; Bildungsangebot; Inklusion; Mehrfachbehinderung; Partizipation; Anwendung; Soziales Netzwerk; Erwachsenenbildung; Lernumgebung; Musikunterricht; Musik; Musizieren; Musikwissenschaft; Medienpädagogik; Lernprozess; Kunstpädagogik; Ästhetische Bildung; Rezension; Bewertung; Bildungsprozess; Empirische Forschung; Deutschland

Entwicklung eines Instruments zur Diagnose der Determinanten freizeitlichen Schreibens von Kindern - Birnbaum, Lisa; Schüller, Elisabeth; Kröner, Stephan (81. Tagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF), 2016)

Freizeitliches Schreiben und Lesen von Kindern im Grundschulalter: Bereichsspezifische Überzeugungen, Geschlecht und Bildungshintergrund als Determinanten - Birnbaum, Lisa (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)
Schreiben und Lesen sind elementare Kulturtechniken, welche Kinder während der Grundschulzeit nicht nur erwerben, sondern auch im Freizeitkontext nutzen. Sie eröffnen den Zugang zu kultureller Teilhabe und können als integraler Bestandteil kultureller Bildung betrachtet werden. Die vorliegende Arbeit geht auf Basis der vier ihr zugrundeliegenden Zeitschriftenartikel der Frage nach, welche Determinanten freizeitliches Schreiben und Lesen von Kindern im Grundschulalter erklären. Um den aktuellen empirischen Forschungsstand zu Determinanten und Kriterien freizeitlichen Schreibens und Lesens von Kindern im Grundschulalter aufzuarbeiten, wurde ein Scoping Review durchgeführt (Birnbaum & Kröner, 2022): Von 982 in Scopus aufgefundenen Originalarbeiten entsprachen n = 62 den Einschlusskriterien. Die meisten dieser Publikationen fokussierten auf das Lesen (n = 58) und nur wenige Arbeiten (n = 4) bezogen sich auch oder ausschließlich auf das Schreiben. Am häufigsten wurden Zusammenhänge von freizeitlichem Schreiben oder Lesen mit bereichsspezifischen Variablen berichtet. Die vorliegende Evidenz bezog sich überwiegend auf korrelative Befunde. Darüber hinaus zeigte sich, dass die meisten Arbeiten nur ausgewählte Determinanten einbezogen, nicht aber eine große Bandbreite. Im Rahmen des Scoping Reviews wurde als Forschungsdesiderat sichtbar, dass eine umfassende empirische Untersuchung einer großen Bandbreite an Determinanten freizeitlichen Lesens und insbesondere Schreibens noch aussteht. Hierauf beziehen sich die drei im Folgenden dargestellten, eigenen empirischen Originalarbeiten. Als theoretisches Rahmenmodell wurde das Person-Umwelt-Transaktionsmodell verwendet, in welchem das Ausmaß kultureller Aktivitäten auf darauf bezogene bereichsspezifische Überzeugungen zurückgeführt wird (untergliedert in den intrinsischen Wert sowie weitere, diesem vorauslaufende verhaltensbezogene, normative und Kontrollüberzeugungen). Die bereichsspezifischen Variablen werden wiederum durch bereichsübergreifende Variablen (wie Geschlecht und Bildungshintergrund) erklärt (Kröner, 2013). Darauf basierend wurde in den ersten beiden Beiträgen die Frage untersucht, welche bereichsspezifischen Überzeugungen Kinder gegenüber freizeitlichen Schreibaktivitäten aufweisen und welche Relevanz bereichsübergreifenden Determinanten zukommt. Letzteres wurde exemplarisch anhand des Geschlechts der Kinder und anhand des Bildungshintergrundes der Mutter untersucht. Im ersten Zeitschriftenartikel wurden im Rahmen von Vorstudien Skalen zu den freizeitlichen Schreibaktivitäten, zum intrinsischen Wert und zu weiteren Überzeugungen entwickelt (Birnbaum et al., 2019). Im zweiten Zeitschriftenartikel wurden die entwickelten Skalen bei einer größeren Stichprobe eingesetzt. Es bestand die Erwartung, dass die vorauslaufenden Überzeugungen zu den Schreibaktivitäten deren intrinsischen Wert erklären, welcher wiederum Varianz in den freizeitlichen Schreibaktivitäten der Kinder aufklären sollte. Außerdem sollten der intrinsische Wert und die weiteren Überzeugungen die Effekte von Geschlecht und Bildungshintergrund der Mutter auf das freizeitliche Schreiben vermitteln. Die Analysen erfolgten mittels Mehrgruppen-Strukturgleichungsmodellen, welche die aufgestellten Hypothesen weitgehend bestätigen konnten: Alle Überzeugungen trugen zur Erklärung freizeitlichen Schreibens bei. Es deuteten sich keine oder allenfalls geringe Effekte des Bildungshintergrunds der Mutter auf die Überzeugungen an. Jedoch zeigte sich, dass Mädchen in ihrer Freizeit mehr und häufiger schreiben als Jungen (Birnbaum, Schüller & Kröner, 2020). Die Geschlechtsunterschiede im freizeitlichen Schreiben konnten vollständig durch die Mittelwertsunterschiede im intrinsischen Wert erklärt werden. In der dritten eigenen empirischen Studie wurden – analog zu den Studien zum freizeitlichen Schreiben – sowohl Analysen zu Effekten einer großen Bandbreite bereichsspezifischer Determinanten als auch zur Relevanz von Geschlecht und Bildungshintergrund der Mutter für freizeitliches Lesen vorgenommen (Schüller et al., 2017). Bei den bereichsspezifischen Determinanten für freizeitliches Lesen zeigte sich die gleiche Faktorenstruktur wie für freizeitliches Schreiben. Durch ein Mehrgruppen-Strukturgleichungsmodell mit dem intrinsischen Wert als Mediator, das analog zu dem Modell zum freizeitlichen Schreiben gebildet wurde, konnte substanzielle Varianz im Ausmaß des freizeitlichen Lesens aufgeklärt werden. Wie in Bezug auf freizeitliches Schreiben waren auch für freizeitliches Lesen die Effekte der bereichsspezifischen Überzeugungen weitaus stärker als die der bereichsübergreifenden Variablen. Ebenso lagen keine oder allenfalls geringe Effekte des Bildungshintergrunds der Mutter vor und es konnten höhere Mittelwerte für Mädchen als für Jungen in allen Skalen nachgewiesen werden. Es gab jedoch auch einen Unterschied zwischen freizeitlichem Lesen und Schreiben: Die Geschlechtsunterschiede im freizeitlichen Lesen konnten – im Vergleich zum freizeitlichen Schreiben – nicht vollständig durch die Mittelwertsunterschiede im intrinsischen Wert erklärt werden. Insgesamt zeigten die empirischen Studien, dass es wichtig es ist, eine große Bandbreite bereichsspezifischer Überzeugungen zu berücksichtigen und dass diese Überzeugungen die Effekte von bereichsübergreifenden Variablen wie Geschlecht und Bildungshintergrund auf freizeitliches Schreiben und Lesen weitgehend vermitteln. Dies spricht sowohl für die entwickelten Überzeugungsskalen als auch für die Eignung des verwendeten Person-Umwelt-Transaktionsmodells als theoretisches Rahmenmodell der empirischen Untersuchungen. Die Wahl des theoretischen Rahmenmodells wird reflektiert. Die zentralen Befunde und die gewählte methodische Vorgehensweise werden diskutiert. Des Weiteren werden Desiderate für die weitere Forschung erschlossen. Abschließend werden zwei Ideen für die weitere Forschung erläutert, die aufbauend auf die vorliegende Arbeit freizeitliches Schreiben und Lesen von Grundschulkindern unter Berücksichtigung des digitalen Wandels und des Empowerments in den Blick nehmen.<br
Keywords: Bildungshintergrund; Geschlecht; Grundschulalter; Kinder; Lesen; Schreiben; Überzeugungen

How to foster writing in children. Development and validation of a family-centered intervention - Birnbaum, Lisa (Internationaler Workshop zur empirischen Bildungsforschung - Extended Education für NachwuchswissenschaftlerInnen, 2016)

Intervening Opportunities between Home and College: Students' Geographic Mobility by College Type - Birnbaum, Lisa; Sonnert, Gerhard; Chen, Chen; Sadler, Philip M.; Kröner, Stephan (Community College Journal of Research and Practice, 2022)
This study compared the geographic mobility of community college students with that of students at other institutions of higher education. Using a sample of 7192 students at 39 institutions across the United States (13 community colleges, 14 public 4-year institutions, 12 private 4-year institutions), it employed the method of operationalizing geographic distance as the number of intervening opportunities between home and school. From normative life course theory, two main hypotheses were derived. Corroborating the first hypothesis, the catchment areas of the community colleges were found to be local and determined by proximity. Contrary to the second hypothesis, there was no interaction effect of gender and college type. Rather, women, on average, exhibited a lower degree of geographic mobility than did their male counterparts across all college types. Although there are certainly structural challenges inherent in the non-hegemonic life course strategy presented by community colleges, community colleges were found to fulfill their mission in terms of delivering an alternative to the hegemonic spatial element of expected geographic mobility in higher education.
CRIS-Team WoS Importer:2022-04-29

Kondensiertes Glück? Komplexe Forschungsdesigns zur Entwicklung musikpädagogischer Interventionen - Birnbaum, Lisa; Flasche, Viktoria; Hasselhorn, Johannes; Jörissen, Benjamin; Kröner, Stephan; Lehmann, Andreas; Lill, Florian; Smolarczyk, Kathrin; Wießnet, Verena (Kulturelle Bildung. Theoretische Perspektiven, methodologische Herausforderungen und empirische Befunde, 2020)

Mobil im Studium – wieso eigentlich (nicht)?! - Birnbaum, Lisa; Müller, Peter; Penthin, Marcus; Kröner, Stephan (Jahrestagung des Zentralinstituts für Lehr-Lernforschung der FAU Erlangen-Nürnberg, 2015)

Musical Leisure Activities in Elementary School Students: The Role of Music-Related Beliefs, Sex, Socioeconomic Status, and Migration Background - Penthin, Marcus; Birnbaum, Lisa; Fritzsche, Eva; Kröner, Stephan (SAGE Open, 2025)
The present study aims to investigate the effects of music-related beliefs on musical leisure activities of elementary school students. To this end, the relationship between music-related beliefs and musical leisure activities was examined while controlling for sex, socio-economic status, and migration background. Data analyses are based on a survey-based study conducted with n = 685 fourth-graders in Germany. Sex and socioeconomic status, but not migration background, explained a small amount of variance in musical leisure activities. After including the music-related beliefs as predictors, they completely mediated the effects of domain-general variables on musical leisure activities and explained 77% of variance in musical leisure activities, with all predictors except the intrinsic value showing unique effects. This work further contributes to the development of reliable and valid scales for the assessment of music-related beliefs. When considering avenues for further research, we emphasize that it is important to incorporate a broad range of music-related beliefs as determinants of leisure musicking in childre
Keywords: beliefs; elementary school children; extracurricular activities; leisure-time activities; musical self-concept; musicking

Place attachment and digitalisation in rural regions - Birnbaum, Lisa; Wilhelm, Carola Rebecca; Chilla, Tobias; Kröner, Stephan (Journal of Rural Studies, 2021)
This paper reflects on place attachment in times of digitalisation in rural regions. Our qualitative study explores the extent to which and with which characteristics place attachment ‘translates’ into the digital format. The paper analyses 193 digital projects presented in the internet. These cases cover several European countries with a particular focus on Germany. The analysis is based on a three-dimensional framework involving attachment concepts, space/place and digitalisation. From a systematic categorisation of the case studies, six result patterns emerge: Some of them confirm place attachment patterns, which are well known from the debate on ‘non-digital’ place attachment (e.g., the importance of emotions). Other findings show that digitalisation does make a difference, in particular concerning abstract, non-localised spatial references to the rural area. Finally, we deduce some implications from our findings for practical implementation in regional development.<br
Keywords: Place attachment; Regional identity; Digitalisation; Rural areas; Sense of place; Regional development

Portfolioarbeit als Bedingungsfaktor für Lern- und Leistungsmotivation - Birnbaum, Lisa (2013)

Schreibaktivitäten von Grundschulkindern – eine empirische Analyse der Determinanten und Fördermöglichkeiten des freizeitlichen Schreibens - Birnbaum, Lisa (GEBF-Nachwuchskonferenz 2016 „Bildungsverläufe im Lebenslauf – Analysen aus der Perspektive verschiedener Disziplinen“, 2016)

The effects of setting and music on the intention to participate in out-of-school music classes: An experimental video vignette study - Smolarczyk, Kathrin; Wießnet, Verena; Birnbaum, Lisa; Kröner, Stephan (Psychology of Music, 2022)
There is a discrepancy between a high inherent value of extracurricular music classes and a low proportion of low-socioeconomic status (SES) male participants. However, evidence on how to match out-of-school music classes to students’ preferences is lacking. Thus, we assessed the attractiveness of different versions of such classes via an experimental video vignette study featuring a 2 × 2-factor (setting × music; each with high vs. low proximity to informal youth culture) between-subjects design with N = 244 students (Grade 5–10). We assessed the intention to participate as criterion, and gender, age, and SES (highest International Socio-Economic Index [HISEI] quartile) as control variables. A hierarchical regression showed a positive effect of music associated with youth culture on intention and no effect of the setting. Female (and older) students displayed higher intention than male (and younger) students. The single effect involving HISEI was a significant interaction of music and SES, which resulted from high-SES adolescents being especially motivated for classes with music associated with youth culture. Thus, to motivate boys and older students in particular, special consideration should be given to the appropriate design and marketing of music classes. However, music close to youth culture might be especially beneficial for adolescents with high rather than low SES.<br
Keywords: intention; music education; youth culture; vignette experiment; out-of-school

The role of parents’ beliefs regarding their children’s literacy acquisition - Ratka-Pauler, Anna; Birnbaum, Lisa; Kröner, Stephan (Frontiers in Education, 2024)
Early literacy acquisition is influenced by children’s social and cultural background. Several empirical studies have shown that by considering literacy activities at home and providing cultural resources, the correlation between the social and cultural background and the children’s literacy achievement can be significantly reduced. This suggests a crucial importance of parents’ beliefs and their role as active agents in the acquisition of literacy skills at home. The aim of the present study is therefore to provide an overview of the range of relevant parental attitudes towards joint literacy activities. In an elicitation study based on the theory of planned behavior, the statements of N = 25 German parents of pre-preschool and preschool children were recorded. All deductive categories based on the theory of planned behavior were confirmed, furthermore the category system could be differentiated inductively. Thus the parental beliefs about joint literacy activities were comprehensively mapped. It is discussed how the explorative results of this study can be used in further studies, for example, to generate a questionnaire based on the TPB to assess parental beliefs for joint literacy activities.
CRIS-Team Scopus Importer:2024-08-02
Keywords: beliefs; early childhood; home learning environment; home literacy environment; home literacy model; parents

Überzeugungen zum freizeitlichen Schreiben bei Grundschulkindern - Birnbaum, Lisa; Schüller, Elisabeth; Kröner, Stephan (Journal for Educational Research Online, 2019)

Überzeugungen zum freizeitlichen Schreiben bei Grundschulkindern – eine qualitative Interviewstudie - Birnbaum, Lisa (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)
Literacy, verstanden als Lese- und Schreikompetenz, vermittelt Grundfähigkeiten, die für die Bewältigung des Alltags notwendig sind. Des Weiteren gilt literacy als Facette kultureller und sozialer Partizipation und ermöglicht die Entfaltung und das zum Ausdruck bringen eigener Gedanken. Diese Kompetenzen werden im Grundschulalter entwickelt und sind darüber hinaus Bestandteil der Freizeitaktivitäten. Welche relevanten Beweggründe zum freizeitlichen Schreiben Grundschulkinder beschreiben, soll in der vorliegenden Arbeit untersucht werden. Ausgehend von der Theorie des geplanten Verhaltens wurden N = 26 Leitfadeninterviews mit Grundschulkindern geführt und inhaltsanalytisch ausgewertet (κ = .90). Die Ergebnisse beziehen sich dabei einerseits auf die Personenseite, bei der insbesondere motivationale Aspekte und das Selbstwirksamkeitserleben der Kinder zentral sind. Andererseits finden sich Überzeugungen, die sich auf die Wahrnehmung der Umwelt und deren subjektiven Widerspiegelung beziehen. Darunter werden neben den sozialen Bezugspersonen die Kontrollierbarkeit der Umgebung verstanden und die Möglichkeiten, die sich dadurch zum Schreiben ergeben. Die Ausdifferenzierung des Kategoriensystems, Grenzen der Studie und mögliche Anschlussforschung werden diskutiert.
Keywords: Grundschulkinder; qualitative Interviewstudie; Schreiben als Freizeitaktivität; Theorie des geplanten Verhaltens

Verortung der Förderrichtlinie DiKuBi und ihrer Vorhaben im Kontext der internationalen Forschung zur Digitalisierung in der kulturellen Bildung. In: Jörissen, B., Kröner, S., Birnbaum, L., Krämer, F. & Schmiedl, F. (2023). Digitalisierung in der kulturellen Bildung: Interdisziplinäre Perspektiven für ein Feld im Aufbruch. - Christ, Alexander; Birnbaum, Lisa; Smolarczyk, Kathrin; Kröner, Stephan (Digitalisierung in der kulturellen Bildung. Interdisziplinäre Perspektiven für ein Feld im Aufbruch, 2023)
Welche Konsequenzen und Potenziale bringt die digitale Transformation für die kulturelle Bildung mit sich? Antworten auf diese Frage bietet der vorliegende Band in Form einer Übersicht über Forschungsergebnisse aus dem BMBF-Förderschwerpunkt „Forschung zur Digitalisierung in der kulturellen Bildung“. Über mehrere Jahre hinweg haben darin 13 Verbund- und Einzelprojekte in ganz Deutschland zu digitalen Phänomenen in der kulturellen Bildung geforscht: zu Musik, Literatur, Tanz, Performance, bildender Kunst und darüber hinaus. Die Forschungsvorhaben zeichnen sich durch eine große Perspektivenvielfalt aus: Neben Erziehungswissenschaft und Bildungsforschung sind spezifische Sparten der kulturellen Bildung und weitere geisteswissenschaftliche Fächer ebenso vertreten wie die wie die Informatik. Zudem hat ein Metavorhaben qualitativ-metatheoretische Perspektiven entwickelt sowie Forschungssynthesen zur Digitalisierung der kulturellen Bildung insgesamt und zum digitalen Wandel einzelner kultureller Aktivitäten erarbeitet, teils unter Verwendung von Big-Data-Methoden. Die im Buch gebündelten Ergebnisse stellen eine wertvolle Ressource für Handelnde in Forschung, Kulturpädagogik und Politik dar, indem sie es ermöglichen, sich einen Überblick über das Innovationspotenzial zu verschaffen, welches sich aus der digitalen Transformation von kultureller Bildung ebenso ergibt wie aus ihrer Erforschung. (DIPF/Orig.)<br
Keywords: Kulturelle Bildung; Digitalisierung; Digitale Medien; Jugendkultur; Forschung; Bildung; Bildungsangebot; Inklusion; Mehrfachbehinderung; Partizipation; Anwendung; Soziales Netzwerk; Erwachsenenbildung; Lernumgebung; Musikunterricht; Musik; Musizieren; Musikwissenschaft; Medienpädagogik; Lernprozess; Kunstpädagogik; Ästhetische Bildung; Rezension; Bewertung; Bildungsprozess; Empirische Forschung; Deutschland

Warum Kinder im Grundschulalter gerne schreiben. Eine Analyse der Determinanten freizeitlichen Schreibens - Birnbaum, Lisa; Schüller, Elisabeth; Kröner, Stephan (Proceedings of the 5. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF), 2017)

What makes elementary students read in their leisure time? Development of a comprehensive questionnaire - Schüller, Elisabeth; Birnbaum, Lisa; Kröner, Stephan (Reading Research Quarterly, 2017)
Why should children read in their leisure time? Reading may contribute to the acquisition of reading literacy and may foster integral human development. However, there has been a scarcity of research on determinants of leisure time reading among elementary school students, especially regarding environmental aspects. In this article, the authors report on the development of a differentiated questionnaire regarding these determinants. Based on a previous series of qualitative and quantitative pilot studies, a study with 980 elementary school students was conducted, applying scales based on behavioral beliefs (motivation in action, thematically congruent consequences, and thematically incongruent costs and benefits), normative beliefs (subjective norm), and control beliefs (self-efficacy and controllability) as predictors of leisure time reading. After excluding motivation in action from analysis because of multicollinearity problems, the variables thematically incongruent costs and benefits, self-efficacy, and controllability explained 50% of variance in the criterion reading frequency. Analyses of covariance indicated that children, especially daughters, of mothers with high educational attainment showed significantly more leisure time reading. The benefits of focusing on students’ beliefs and of including environmental aspects in research on leisure time reading are discussed.<br
Keywords: Assessment; Standardized; Motivation; Engagement; Attitude; Extrinsic; Intrinsic; Self-efficacy; Research methodology; Mixed methods; Theoretical perspectives; Behavioral; Childhood

What makes primary school students write? A longitudinal study on recreational writing and its determinants. - Birnbaum, Lisa; Schüller, Elisabeth; Kröner, Stephan (Summer School des Zentralinstituts für Lehr-Lernforschung, 2016)

What’s next. Perspektiven für ein erweitertes Verständnis von (digitaler) kultureller Bildung. In: Jörissen, B., Kröner, S., Birnbaum, L., Krämer, F. & Schmiedl, F. (2023). Digitalisierung in der kulturellen Bildung: Interdisziplinäre Perspektiven für ein Feld im Aufbruch. - Kröner, Stephan; Birnbaum, Lisa; Klepacki, Leopold (Digitalisierung in der kulturellen Bildung. Interdisziplinäre Perspektiven für ein Feld im Aufbruch, 2023)
Welche Konsequenzen und Potenziale bringt die digitale Transformation für die kulturelle Bildung mit sich? Antworten auf diese Frage bietet der vorliegende Band in Form einer Übersicht über Forschungsergebnisse aus dem BMBF-Förderschwerpunkt „Forschung zur Digitalisierung in der kulturellen Bildung“. Über mehrere Jahre hinweg haben darin 13 Verbund- und Einzelprojekte in ganz Deutschland zu digitalen Phänomenen in der kulturellen Bildung geforscht: zu Musik, Literatur, Tanz, Performance, bildender Kunst und darüber hinaus. Die Forschungsvorhaben zeichnen sich durch eine große Perspektivenvielfalt aus: Neben Erziehungswissenschaft und Bildungsforschung sind spezifische Sparten der kulturellen Bildung und weitere geisteswissenschaftliche Fächer ebenso vertreten wie die wie die Informatik. Zudem hat ein Metavorhaben qualitativ-metatheoretische Perspektiven entwickelt sowie Forschungssynthesen zur Digitalisierung der kulturellen Bildung insgesamt und zum digitalen Wandel einzelner kultureller Aktivitäten erarbeitet, teils unter Verwendung von Big-Data-Methoden. Die im Buch gebündelten Ergebnisse stellen eine wertvolle Ressource für Handelnde in Forschung, Kulturpädagogik und Politik dar, indem sie es ermöglichen, sich einen Überblick über das Innovationspotenzial zu verschaffen, welches sich aus der digitalen Transformation von kultureller Bildung ebenso ergibt wie aus ihrer Erforschung. (DIPF/Orig.)<br
Keywords: Kulturelle Bildung; Digitalisierung; Digitale Medien; Jugendkultur; Forschung; Bildung; Bildungsangebot; Inklusion; Mehrfachbehinderung; Partizipation; Anwendung; Soziales Netzwerk; Erwachsenenbildung; Lernumgebung; Musikunterricht; Musik; Musizieren; Musikwissenschaft; Medienpädagogik; Lernprozess; Kunstpädagogik; Ästhetische Bildung; Rezension; Bewertung; Bildungsprozess; Empirische Forschung; Deutschland

Who likes to engage in writing? - The role of children's beliefs and intrinsic value regarding leisure writing - Birnbaum, Lisa; Schüller, Elisabeth; Kröner, Stephan (Educational Psychology, 2020)
While leisure writing may help children to acquire writing skills, it can also be considered as an inherently valuable cultural activity. This study explores how children’s beliefs may explain to what extent children are inclined to leisure writing and if there are any gender differences. Building on preliminary scale development work, we analysed data from 963 third-graders. Variables included (a) the intrinsic value attached to leisure writing (b) preceding behavioural, normative, and control beliefs related to these activities, and (c) the level of leisure writing. In a structural equation model, the preceding beliefs were applied as explanatory variables for the intrinsic value. Intrinsic value, in turn, explained a large proportion of variance in children’s leisure-writing activities. Gender differences in leisure writing were mediated by intrinsic value. Significance of intrinsic value and preceding beliefs regarding leisure-writing activities are discussed.<br
CRIS-Team WoS Importer:2020-07-17
Keywords: Elementary school students; intrinsic value; literacy; leisure writing